Price Perception and E-WOM Effects on Brand Image and Purchase Intention in Air India - Aisyah Rahmawati; Teuku Alwi Isyan; Abdul Ghafar; Deslida Saidah; Vica Nurhayani Harahap (Dinasti International Journal of Education Management and Social Science, 2026)
This research was conducted to find out the influence of Price and Electronic Word of Mouth (e-WOM) through Brand Image as an intervening variable on Purchase Intention in Air India Airlines. The population in this study were respondents from various countries who had prior experience and familiarity with Air India. The study employed purposive sampling and adopted a quantitative design using SEM-PLS through SmartPLS. A total of 200 responses were collected via structured questionnaires. The results show that both Price and e-WOM significantly impact Brand Image. However, e-WOM does not significantly affect Purchase Intention, directly or indirectly, while Price and Brand Image have a significant direct influence on Purchase Intention. This study contributes to the literature on airline marketing by highlighting the mediating role of brand image in emerging markets, offering strategic insights for airlines seeking digital reputation recovery.